Traditional Acehnese House: Constructing Architecture by Responding to the Power of Nature in Relation to the Local Wisdom Values - Izziah Izziah; Laina Hilma Sari; Erna Meutia; Mirza Irwansyah (Aceh International Journal of Science and Technology, 2020)
The existence of traditional houses in Banda Aceh has been extinguished in modern times. With globalization's impact, the traditional house connotates as ‘old house style,’ and thus, the house style is not up to date. A large number of house owners demolish them and reconstruct them with new modern houses. Despite that, it is approved that the traditional houses of Aceh were survived the earthquake that frequently hit the region. As Banda Aceh is one of the regions resided on Sumatran's segment, the region has a large number of earthquakes.  This paper, which is part of the previous study on the thermal comfort of traditional and modern houses in Aceh, explores a historical architectural example that reveals local experiences that involve local wisdom and expertise. This paper focuses on a traditional house located in a modern housing neighborhood in Banda Aceh city. In doing this, the paper identifies how Acehnese ancestors, through their local knowledge, have constructed a traditional Acehnese house. The article also shows how its architectural form's construction techniques respond to the region's geographical condition. In constructing this study, interview and observation toward the building as primary data collections are conducted. Also, several written sources, as secondary data, related to an Acehnese traditional house, are reviewed. This paper shows that constructing a conventional house is a responsive architecture toward hot climate and earthquake. Therefore, this architectural building type with the local wisdom value's involvement is worthy of being applied and adapted in modern life.